The Influence of Career Adaptability and Career Management Perception in Improving Career Success - Endriawan Hadi; Edy Raharja (Journal of Business, Social and Technology, 2023)
The purpose of this research is to test the influence of competence on career management perception, career adaptability to impact career success. Using these variables, the use of these variables is able to solve the problems arising withinJunior Engineerand Junior Process Engineeroil and gas company in Indonesia Statement of this problem is how to increase career success?. The sample size of this research is 189Junior Engineerand Junior Process Engineeroil and gas company in Indonesia. Using the Smart PLS. The results show that competence in career management perception, career adaptability to impact career success.The effect ofcompetenceon e career success is significant;the effect ofcompetenceon career management perception are significant;the effect ofcompetenceon career adaptability are significant;the effect ofcareer management perception on career success is significant;the effect ofcareer adaptabilityon career success are significant.